Indonesia's Downstream Diplomacy Strategy Through BRICS Membership - Larasati Larasati; Elyana Ade Pertiwi (Insignia: Journal of International Relations, 2026)
Abstract As an effort to increase economic independence and export value, strategic natural resource hilirisasi diplomacy is a top priority for Indonesia. Indonesia's membership in BRICS in 2025 will open-up opportunities for the country to design a roadmap for advanced commercial diplomacy and utilize this forum to increase market diversification, attract investment, and foster technological collaboration. This article examines Indonesia's steps in developing a long-term diplomatic plan through BRICS while upholding the principle of an "independent and active" foreign policy. This paper will examine Indonesia's position as a middle power attempting to balance national interests with the demands of the evolving international system using the framework of a commercial diplomacy approach and role theory in a case study of the nickel export ban at the WTO. It will also examine Indonesia's stance on the BRICS economic agenda, which is considered an alternative instrument to strengthen Indonesia's bargaining position against pressure from Western countries. The findings in this paper indicate that BRICS can be a strategic vehicle for Indonesia's downstream diplomacy. However, its success depends on Indonesia's ability to play a constructive role in the global competitive arena. The results show that downstream diplomacy is an important part of Indonesia's foreign policy strategy in an increasingly multipolar world era, rather than simply a national economic issue. Keywords: BRICS, Commercial Diplomacy, Downstream Diplomacy, Indonesia Foreign Policy, Role Theory Abstrak Sebagai upaya meningkatkan kemandirian ekonomi dan nilai tambah ekspor, diplomasi hilirisasi sumber daya alam strategis merupakan prioritas utama Indonesia. Dengan masuknya Indonesia sebagai anggota BRICS pada tahun 2025. Hal ini akan membuka peluang Indonesia dalam merancang roadmap diplomasi komersial lanjutan serta memanfaatkan forum ini untuk meningkatkan diversifikasi pasar, menarik investasi, dan mendorong kolaborasi teknologi. Melalui artikel ini, penulis menelaah langkah Indonesia dalam membuat rencana diplomasi jangka panjangnya melalui BRICS sambil mempertahankan prinsip kebijakan luar negeri bebas-aktif. Tulisan ini akan mengkaji posisi Indonesia sebagai kekuatan menengah yang mencoba menyeimbangkan kepentingan nasional dengan tuntutan sistem internasional yang berkembang dengan menggunakan kerangka pendekatan diplomasi komersial dan role theory dalam studi kasus larangan ekspor nikel di WTO. Beserta sikap Indonesia terhadap agenda ekonomi BRICS yang dianggap sebagai instrumen alternatif untuk meningkatkan posisi tawar Indonesia terhadap tekanan dari negara-negara Barat. Temuan dalam tulisan ini menunjukkan bahwa BRICS dapat menjadi wahana strategis untuk diplomasi hilirisasi Indonesia. Meskipun, keberhasilannya bergantung pada kemampuan Indonesia memainkan peran konstruktif dalam arena persaingan global. Hasilnya menunjukkan diplomasi hilirisasi merupakan bagian penting dari strategi kebijakan luar negeri Indonesia di era dunia yang semakin multipolar daripada sekadar masalah ekonomi nasional. Kata kunci: BRICS, diplomasi hilirisasi, diplomasi komersil, kebijakan luar negeri Indonesia, teori peran